Drivers of passive leadership in wild songbirds: species-level differences and spatio-temporally dependent intraspecific effects - Gokcekus, S; Firth, JA; Regan, C; Cole, EF; Lamers, KP; Sheldon, BC (Springer, 2021)
Collective behaviors are typical for many social species and can have fitness benefits for participating individuals. To maximize the benefits obtained from group living, individuals must coordinate their behaviors to some extent. What are the mechanisms that make certain individuals more likely to initiate collective behaviors, for example, by taking a risk to initially access a resource (i.e., to act as “leaders”)? Here, we examine leading behavior in a natural population of great tits and blue tits. We use automated feeding stations to monitor the feeder visits of tagged individuals within mixed-species flocks, with a small cost (waiting < 2 s) associated with the initial unlocking of the feeder. We find that great tits, males, and individuals with high activity levels were more likely to be leading in each of their feeder visits. Using a null model approach, we demonstrate that the effects of sex and activity on passive leading behavior can be explained by patterns of spatial and temporal occurrence. In other words, these effects can be explained by the times and locations of when individuals visit rather than the actual order of arrival. Hence, an analysis of the causes of leading behavior is needed to separate the effects of different processes. We highlight the importance of understanding the mechanisms behind leading behavior and discuss directions for future experimental work to gain a better understanding of the causes of leadership in natural populations.